Lombard Independent-Mindedness in the Face of Uncertainty: Coping with the Unpredictable Present Future in Lombard Southern Italian Narratives (9th–10th Centuries) - Bart Peters (On_Culture, 2023)
Ninth- and tenth-century Southern Italy was a crossroads where the Franks, the Byzantines, the Roman Popes, and the emirs of Sicily sought to increase their influence. The rivaling Lombard princes in Benevento, Capua, and Salerno had to cope with each other and these external pressures. That combination created unease and tension for the immediate future of the present of the ninth-century Lombard monk Erchempert and the chronicle of Salerno’s anonymous tenth-century author. Although a century apart, they lived through a very uncertain present. Islamic raiders destroyed Erchempert’s abbey of Montecassino in 883, and the Salernitan text abruptly ended amidst a revolt against the reigning prince Gisulf I in the 970s. The chaotic nature of their present influenced both authors’ attempts to instruct future readers through a narrative focusing on the exemplary military conduct of specific Lombard princes. This contribution will consist of close readings of such martial scenes featuring exemplary Lombard princes from both texts. It will be argued that the Lombard lords in these scenes served as idealized examples evoking a strong sense of Lombard independent-mindedness in the face of an unpredictable present. While their strong sense of independence has been noted in previous scholarship, comparing its manifestation in the two narrative texts has yet to receive a dedicated study. The article will reveal and compare how these texts, in an uncertain present, clung to an exemplary past, attempting to steer their unpredictable present’s future.